Financial frictions and the SME investment gap: new survey evidence for Ireland. Issue 3 (2nd July 2020) - Martinez-Cillero, Maria; Lawless, Martina; O'Toole, Conor; Slaymaker, Rachel
ABSTRACT: In this paper, we use novel firm-level survey data on investment expenditure for Irish SMEs to investigate the existence of investment constraints between 2016 and 2018. We model investment as a function of firms' economic fundamentals and factors affecting firms' access to finance. We use an empirical version of the traditional fundamental Q model which links investment to the marginal returns to capital. Empirically we deploy a two-stage Heckman model and include measures of financial frictions such as access to collateral, non-bank financing, internal finance and indebtedness. We find evidence that investment is substantially lower than the level suggested by economic fundamentals alone and that a considerable financing gap is evident. On average, we find that investment could be 55% higher than present if financing constraints were completely eliminated.